2023
DOI: 10.1093/bioinformatics/btad390
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable deep learning architectures for improving drug response prediction performance: myth or reality?

Abstract: Motivation Interpretable deep learning (DL) models that can provide biological insights, in addition to accurate predictions, are of great interest to the biomedical community. Recently, interpretable DL models that incorporate signaling pathways have been proposed for drug response prediction. While these models improve interpretability, it is unclear whether this comes at the cost of less accurate drug response predictions, or a prediction improvement can also be obtained. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In an attempt to make models more interpretable, biological knowledge is often explicitly encoded into prediction models, e.g. using pathway-layers in neural networks [ 4 , 35 , 67 ], exploiting known protein interactions [ 22 ] or encoding information on known markers of drug response [ 11 ]. Li et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to make models more interpretable, biological knowledge is often explicitly encoded into prediction models, e.g. using pathway-layers in neural networks [ 4 , 35 , 67 ], exploiting known protein interactions [ 22 ] or encoding information on known markers of drug response [ 11 ]. Li et al .…”
Section: Resultsmentioning
confidence: 99%
“…Li et al . found, however, that the explicit incorporation of biological knowledge may decrease model performance and lead to false conclusions [ 35 ]. Hence, the assumptions that are introduced by adding biological knowledge to a model should be carefully investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, existing methods rarely compare themselves against simpler baseline models, making the superiority of highly complex models questionable. Third, it can be shown that even a simple mean predictor, which just reports mean drug response in the training data, can achieve surprisingly good performance, questioning whether current methods actually learn cell-line specific drug response as advertised and whether current performance measures are adequate [63]. Indeed, it can be shown that the current practice of reporting the correlation between predicted and observed drug response across all drugs is subject to Simpson's paradox (Figure 2) due to drug-specific average responses.…”
Section: Judith Bernett Markus Listmentioning
confidence: 99%
“…None of these benchmarks use any omics data or drug structures. We note that the drug and CL average benchmarks have recently been shown to have strong performance (Branson et al, 2023;Li et al, 2023) Where n Dtrainc is the number of drug cell line pairs in the training set that include c.…”
Section: Null Hypothesis Benchmarksmentioning
confidence: 99%